Corrosion behaviour of WC-10% AISI 304 cemented carbides. (November 2015) - Oliveira, A.B.; Bastos, A.C.; Fernandes, C.M.; Pinho, C.M.S.; Senos, A.M.R.; Soares, E.; Sacramento, J.; Zheludkevich, M.L.; Ferreira, M.G.S.
Highlights: WC composites have been produced with AISI 304L as metallic binder. The corrosion resistance is comparable to the WC–Co benchmark. The localized corrosion process was analyzed by SEM and SVET. Abstract: The corrosion behavior of tungsten carbide hard metal composites with AISI 304L stainless steel as binder matrix and a WC–Co composite with similar grain size and binder content was investigated using electrochemical techniques (open circuit potential monitoring, current-potential curves, electrochemical impedance spectroscopy, scanning vibrating electrode technique) and scanning electron microscopy.